Randomised controlled trial of a nurse coordination intervention for people living with dementia and their carers: study protocol - John Attia; Jennifer White; Christopher Oldmeadow; Joel J Rhee; Simon Deeming; Michelle Kelly; Anna Williams; Kylie Wales; Yun-Hee Jeon; John Ward; Dimity Pond; Kate Wood; et al. (BMJ Open)
Introduction The multifaceted impact of dementia means that people living with dementia require multidisciplinary care across different services and settings; however, these care transitions pose a risk of fragmented care. Models that improve integration and coordination of care in the community are needed.Methods and analysis This randomised control trial will test the effectiveness and cost effectiveness of a dementia nurse-led intervention to: (1) increase days lived in the community at 12-month follow-up (primary outcome) among people living with dementia and (2) improve quality of life for people living with dementia and their carers, compared with usual care. Participants are recruited from several sources including private and public geriatric medicine clinics, carer support groups and self-referral. People living with dementia and their carers are randomised as a dyad to (1) usual care or (2) dementia nurse-led care-coordination. The dementia nurse will provide care coordination and direct support through a tailored, integrated and patient-centred approach. The needs of people living with dementia will be identified and addressed, with a focus on improving the management of comorbidities, risk reduction and symptoms. Carers will also receive support. The model for people living with dementia will focus on days lived in their community as the outcome variable. Differences between groups in quality of life at 12-month follow-up will be assessed using linear mixed effects regression. Analysis will follow the intention to treat principles. People living with dementia and carers’ data will be analysed separately and collectively for the economic study.Ethics and dissemination The trial has been approved by the Hunter New England Research Ethics Committee (2023/ETH01221) and the University of Newcastle Ethics Committee (R-2024–0021). Trial findings will be disseminated via peer-reviewed publications and conference presentations. If the intervention is effective, the research team aims to further implement the intervention as usual care within the participating services and beyond.Trial registration number The trial was prospectively registered via the Australian New Zealand Clinical Trials Registry: ACTRN12624000235505. Registration date: 11 March 2024.